2016
DOI: 10.1177/0363546516629419
|View full text |Cite
|
Sign up to set email alerts
|

How Young Girls Change Their Landing Technique Throughout the Adolescent Growth Spurt

Abstract: The outcomes of this research provide a greater understanding of the changes in the landing strategy used by pubescent girls throughout the adolescent growth spurt. This can assist in the development of screening tools designed to determine "at-risk" landing biomechanics during puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Riskier knee biomechanics characteristic of post-pubertal females (reduced flexion; greater peak valgus angles and moments) emerge during puberty, and thus age at menarche may serve in part as a simple proxy for the timing of these neuromuscular developments. [11][12][13][14][15]20,50,51 The observed effect of earlier menarche could therefore be nothing more than an artifact of longer exposure to riskier postpubertal movement patterns: for a given age, athletes who entered the post-pubertal period of higher risk earlier would have naturally accrued greater cumulative years of injury risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riskier knee biomechanics characteristic of post-pubertal females (reduced flexion; greater peak valgus angles and moments) emerge during puberty, and thus age at menarche may serve in part as a simple proxy for the timing of these neuromuscular developments. [11][12][13][14][15]20,50,51 The observed effect of earlier menarche could therefore be nothing more than an artifact of longer exposure to riskier postpubertal movement patterns: for a given age, athletes who entered the post-pubertal period of higher risk earlier would have naturally accrued greater cumulative years of injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 Divergent pubertal developmental trajectories in males and females likely underlie a suite of high-risk traits that appear widely in post-pubertal females, but less commonly in males. [11][12][13][14][15][16][17][18][19][20] Despite these broad sex-based distinctions, the process of puberty in terms of rates and timing of growth events is highly variable within each sex. Variation in pubertal development may therefore have effects on variability in ACL injury risk factors within females.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks for all moments were derived and exported for analysis. Joint moments were evaluated during the first 25% of stance as ACL injury typically occurs shortly after initial contact [ 4 ]. Anthropometric segment lengths for the thigh and shank were extracted from the kinematic model.…”
Section: Methodsmentioning
confidence: 99%
“…19,30 A substantial body of literature has shown that postpubertal females exhibit a tendency toward more valgus knee angles and loading than do males during the DVJ. 10,16,21,23,27,63 Greater valgus angulation and loading among females generate high frontal plane shear stress on the ACL, 26 making "valgus collapse" the most common mode of female injuries. 48 There also appears to be a relationship between the timing of pubertal development and the emergence of biomechanical risk factors in females.…”
mentioning
confidence: 99%